2015
DOI: 10.4238/2015.august.14.27
|View full text |Cite
|
Sign up to set email alerts
|

Estimating the genetic parameters for liver fat traits in broiler lines divergently selected for abdominal fat

Abstract: ABSTRACT. Intensive selection of broilers for improved growth rate is known to exert a negative effect on broiler health, such as an increase in body fat (and its related diseases). Excessive fat deposition in the liver can cause fatty liver hemorrhagic syndrome (FLHS); in addition, traits associated with liver fat have also been associated with FLHS. This study explored the genetic relationships among liver fat-related traits. Data was collected from 462 birds derived from 16th generation Northeast Agricultur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 33 publications
0
6
0
1
Order By: Relevance
“…The liver is an important organ for the synthesis and accumulation of fat and has a regulatory role in lipid metabolism ( Ma et al, 2018 ). During the past few decades, intensive genetic selection breeding in commercial broilers has gained satisfactory achievements in increased growth rates and egg production, but also led to undesirable fat deposition ( Liang et al, 2015 ; Resnyk et al, 2017 ). Excessive fat deposition in broilers has thus become a major problem in today’s broiler industry, with the reason that it causes a reduction on the carcass yield and feed efficiency, and loss of consumers’ favor for the meat as well ( Wang et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…The liver is an important organ for the synthesis and accumulation of fat and has a regulatory role in lipid metabolism ( Ma et al, 2018 ). During the past few decades, intensive genetic selection breeding in commercial broilers has gained satisfactory achievements in increased growth rates and egg production, but also led to undesirable fat deposition ( Liang et al, 2015 ; Resnyk et al, 2017 ). Excessive fat deposition in broilers has thus become a major problem in today’s broiler industry, with the reason that it causes a reduction on the carcass yield and feed efficiency, and loss of consumers’ favor for the meat as well ( Wang et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…However, modern broiler strains often tend to have excessive abdominal fat deposit12, which needs to be controlled, since it has a negative impact on poultry production, as evidenced by the increase in feed cost during rearing, decrease in the final meat quality, and the significant economic loss to poultry-processing plants345. Due to the economic concerns and consumer aversion to excess fat deposition, excess fat control and improvement of meat quality are important topics of research for poultry scientists.…”
mentioning
confidence: 99%
“…Chicken stores energy as neutral fats mainly in the adipocytes of the abdominal fat pad. Although it was not observed hepatic lipidosis in HFD-fed hens, the results from a previous study have shown that the abdominal fat weight is positively correlated with the liver fat percentage in selected broilers [36]. The different findings could be related to multiple factors including the genetic background of chickens and their age as well as the sample size.…”
Section: Discussionmentioning
confidence: 73%